Visual Exploration at Higher Fixation Frequency Increases Subsequent Memory Recall. Issue 1 (21st July 2020) - Fehlmann, Bernhard; Coynel, David; Schicktanz, Nathalie; Milnik, Annette; Gschwind, Leo; Hofmann, Pascal; Papassotiropoulos, Andreas; de Quervain, Dominique J-F
Abstract: Only a small proportion of what we see can later be recalled. Up to date it is unknown how far differences in visual exploration during encoding affect the strength of episodic memories. Here, we identified individual gaze characteristics by analyzing eye tracking data in a picture encoding task performed by 967 healthy subjects during fMRI. We found a positive correlation between fixation frequency during visual exploration and subsequent free recall performance. Brain imaging results showed a positive correlation of fixation frequency with activations in regions related to vision and memory, including the medial temporal lobe. To investigate if higher fixation frequency is causally linked to better memory, we experimentally manipulated visual exploration patterns in an independent population of 64 subjects. Doubling the number of fixations within a given exploration time increased subsequent free recall performance by 19%. Our findings provide evidence for a causal relationship between fixation frequency and episodic memory for visual information.